A method for improving stability of a chamber wall and a plasma processing apparatus

CN122979872APending Publication Date: 2026-10-27SHANGHAI BANGXIN SEMI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611467362.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是阳极氧化铝涂层存在纳米孔道,会显著吸附水汽和反应气体以及副产物残留,影响H/F自由基浓度的稳定性,因此还会对阳极氧化铝涂层进行表面封孔处理,以降低阳极氧化铝涂层中垂直毛细管/蜂窝状的孔隙

Benefits of technology

(1)通过对内衬件表面的阳极氧化铝层进行水合封孔处理形成水合氧化铝(勃姆石)层,并使水合氧化铝层发生脱水缩合和相变反应形成致密化的伽马氧化铝(γ-Al2O3)层,可将内衬件在腔体中的服役期间必然发生的有害相变(水合氧化铝在腔体150℃~500℃的工作温度下必然会发生脱水收缩-应力漂移-微裂纹-颗粒产生),通过预先施加的真空烘烤处理提前一次性完成并固化,使安装内衬件后的腔体壁面状态在进行等离子体处理工艺前就进入热力学稳定状态(从“被动承受壁面老化”转为“主动消除老化源”)。从而实现从颗粒产生的源头进行了有效规避,提升了腔体壁面在含氢和含氟等离子体环境下的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979872A_ABST
    Figure CN122979872A_ABST
Patent Text Reader

Abstract

The application discloses a method for improving cavity wall stability and a plasma processing device, and relates to the technical field of plasma processing devices, in particular to a method for improving cavity wall stability and a plasma processing device. The method comprises the following steps: providing an inner lining with an anodic aluminum oxide layer on a working side surface; performing a hydration sealing treatment on the surface of the anodic aluminum oxide layer by using water vapor to form a hydrated aluminum oxide layer; performing a vacuum baking treatment to make the hydrated aluminum oxide layer undergo dehydration condensation and phase change reaction to form a densified gamma aluminum oxide layer; sequentially forming an aluminum oxide cap layer, a yttrium oxide cap layer and a yttrium fluoride cap layer on the surface of the gamma aluminum oxide layer by using an atomic layer deposition process; and installing the inner lining on the inner wall of a cavity to perform at least one of a hydrogen-containing plasma processing process and a fluorine-containing plasma processing process. By constructing a carbon-free all-inorganic wall surface protection system with a multi-layer dense laminated structure, the application can improve the concentration stability of H and F free radicals in the cavity and particle peeling defects, and realizes the stabilization of the cavity wall.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of semiconductor processing technology, and in particular to a method for improving cavity wall stability and a plasma processing apparatus. Background Technology

[0002] If the inner wall material (lining) of a semiconductor reaction chamber is made of aluminum, a hard oxide coating (anodized aluminum oxide layer) is typically added to its surface. Compared to the bare aluminum surface, the addition of a hard oxide coating can, to some extent, reduce the bombardment and erosion damage of plasma (hydrogen / fluorine processes) on the inner wall surface (the hard oxide coating thickness can reach tens of micrometers, approximately 15,000 times the thickness of the natural oxide layer, and its density is approximately 5 times that of the natural oxide layer, theoretically enhancing the protection of the underlying aluminum by nearly 5 orders of magnitude). When the inner wall surface of the chamber is eroded by H / F free radicals, it releases aluminum oxide rather than metallic Al, thus providing a certain degree of protection. However, the anodized aluminum oxide coating has nanopores, which can significantly adsorb water vapor, reaction gases, and byproduct residues, affecting the stability of the H / F free radical concentration. Therefore, the anodized aluminum oxide coating is also subjected to surface sealing treatment to reduce the vertical capillary / honeycomb porosity in the anodized aluminum oxide coating. However, even after sealing, some porosity usually remains. In a highly reactive H / F-containing plasma and free radical environment, this can still cause some loss of the inner wall surface of the cavity, leading to particle shedding and instability in free radical concentration, which in turn affects the instability of the process results in hydrogen- and fluorine-containing processes. Therefore, it is necessary to study a process method that can significantly improve the above problems. Summary of the Invention

[0003] The purpose of this application is to overcome the aforementioned problems in the prior art and to provide a method for improving cavity wall stability and a plasma processing device for use in hydrogen- and fluorine-containing processes, so as to improve the stability of free radical concentration and improve particulate defects.

[0004] To achieve the above objectives, the technical solution of this application is as follows: According to a first aspect of this application, embodiments of this application provide a method for improving cavity wall stability, comprising: A cavity liner is provided, the liner material is aluminum alloy, and the working side surface of the liner has an anodized aluminum layer; Using water vapor, the surface of the anodic aluminum oxide layer is hydrated and sealed to form a hydrated aluminum oxide layer on the surface of the anodic aluminum oxide layer. Vacuum baking is performed to cause the hydrated alumina layer to undergo dehydration condensation and phase transformation reaction, forming a dense gamma alumina layer. Using atomic layer deposition, an alumina cap layer, a yttrium oxide cap layer, and a yttrium fluoride cap layer are sequentially formed on the surface of the gamma alumina layer; The liner is installed on the inner wall of a cavity used to perform at least one of a hydrogen-containing plasma treatment process and a fluorine-containing plasma treatment process.

[0005] In some embodiments, the water vapor is prepared using deionized water, and an anti-ashing agent is added to the water vapor. The water vapor has an electrical conductivity of less than 2 μS / cm and a chloride ion content of less than 1 ppm. When performing the hydration sealing treatment, the temperature is 100℃~115℃, the pressure is 0.02MPa~0.05MPa, and the time is 2min / μm~3min / μm.

[0006] In some embodiments, the anti-ashing agent includes triethanolamine added at an amount of 0.5 g / L to 2 g / L.

[0007] In some embodiments, after the hydration sealing treatment, the surface of the liner is rinsed with deionized water for 25 to 35 seconds and dried with nitrogen. Then, the surface of the liner is subjected to ultrasonic-assisted descaling treatment with a volume concentration of 15% to 20% nitric acid solution at room temperature for 30 to 60 seconds at an ultrasonic frequency of 35 kHz to 45 kHz. Afterward, the surface of the liner is ultrasonically rinsed multiple times with deionized water until the resistivity of the deionized water after the final ultrasonic rinsing reaches 15 MΩ·cm or higher, and then dried with nitrogen.

[0008] In some embodiments, the vacuum baking process is performed when the vacuum degree is less than 1×10⁻⁶. -3 Torr, with a heating rate of 2℃ / min to 5℃ / min, a first plateau temperature of 200℃ to 350℃, a first plateau holding time of 50min to 70min, a second plateau temperature of 450℃ to 550℃, a second plateau holding time of 2 hours to 4 hours, a cooling rate of less than 5℃ / min, and a furnace exit temperature of less than 100℃.

[0009] In some embodiments, when forming the alumina cap layer, the first precursor includes trimethylaluminum, the second precursor includes H2O, the temperature is 200℃~250℃, the number of cycles is 300 to 500, the introduction time of the first precursor is 0.05s~0.1s in each cycle, the introduction time of the second precursor is 0.05s~0.1s, and the single purging time is 10s~20s.

[0010] In some embodiments, the thickness of the alumina cap layer is 30 nm to 50 nm.

[0011] In some embodiments, when forming the yttrium oxide cap layer, the first precursor includes tris(2,2,6,6-tetramethyl-3,5-heptadecyl)yttrium, the second precursor includes O3, the temperature is 250°C to 350°C, the number of cycles is 1000 to 2000, the introduction time of the first precursor is 0.5s to 2s per cycle, the introduction time of the second precursor is 1s to 3s, and the single purging time is 20s to 60s.

[0012] In some embodiments, the thickness of the yttrium oxide cap layer is 40 nm to 80 nm.

[0013] In some embodiments, when forming the yttrium fluoride cap layer, the first precursor includes tris(2,2,6,6-tetramethyl-3,5-heptadecyl)yttrium, the second precursor includes TiF4, the temperature is 175°C to 325°C, the number of cycles is 350 to 550, the introduction time of the first precursor is 0.5s to 2s per cycle, the introduction time of the second precursor is 0.5s to 2s, and the single purging time is 20s to 60s.

[0014] In some embodiments, the thickness of the yttrium fluoride cap layer is 40 nm to 80 nm.

[0015] In some embodiments, after the alumina cap layer, the yttrium oxide cap layer, and the yttrium fluoride cap layer are formed, each is subjected to an annealing treatment.

[0016] In some embodiments, the annealing process includes vacuum annealing at a temperature of 280°C to 320°C for 1 to 2 hours.

[0017] According to a second aspect of this application, embodiments of this application also provide a plasma processing apparatus, including a cavity, wherein an inner liner is provided on the inner wall of the cavity, and the inner liner is obtained using a method for improving cavity wall stability as provided in any of the embodiments of the first aspect above.

[0018] The embodiments of this application may have, or at least have, the following advantages: (1) By performing hydration sealing treatment on the anodic aluminum oxide layer on the surface of the liner to form a hydrated aluminum oxide (boehmite) layer, and then causing the hydrated aluminum oxide layer to undergo dehydration condensation and phase transformation reaction to form a dense gamma-alumina (γ-Al2O3) layer, the harmful phase transformation that will inevitably occur during the service of the liner in the cavity (hydrated aluminum oxide will inevitably undergo dehydration shrinkage-stress drift-microcracks-particle generation at the working temperature of 150℃~500℃ in the cavity) can be completed and cured in advance by a vacuum baking treatment. This allows the cavity wall after the liner is installed to enter a thermodynamically stable state before the plasma treatment process (from "passively enduring wall aging" to "actively eliminating aging sources"). This effectively avoids the source of particle generation and improves the stability of the cavity wall in hydrogen- and fluorine-containing plasma environments.

[0019] (2) By performing sealing and baking treatment, the density of the anodic aluminum oxide layer on the surface of the inner liner is improved. Furthermore, by using atomic layer deposition on the surface of the dense anodic aluminum oxide layer, a multi-layer stacked structure of high-density aluminum oxide cap layer, yttrium oxide cap layer and yttrium fluoride cap layer is formed, forming a protection system with multiple protective layers. This improves the protection capability of the inner liner surface, reduces the probability of H and F plasma / free radicals invading the inner wall surface, and thus reduces the residue and reaction inside the porous structure of the anodic aluminum oxide layer. This improves the concentration stability of H and F free radicals in the cavity and achieves cavity wall stabilization under hydrogen-containing plasma and fluorine-containing plasma treatment processes.

[0020] (3) By using water vapor mixed with an anti-ashing agent to seal the surface of the anodic aluminum oxide layer of the inner lining, the generation of surface flocculents can be reduced. By controlling the sealing time according to the thickness of the anodic aluminum oxide layer, the problems of incomplete sealing due to insufficient sealing time or increased surface flocculents due to excessive sealing time can be avoided. By using nitric acid solution for deashing treatment at room temperature, the structure of the hydrated aluminum oxide layer can be avoided due to excessive temperature. By controlling the ultrasonic frequency, the residue at the orifice can be peeled off at low power. By controlling the deashing treatment time, only the surface flocculents can be dissolved, and the hydrated aluminum oxide layer can be avoided. Baking under vacuum allows for faster dehydration and prevents re-moistening. Controlling the heating rate prevents microcracks caused by stress concentration during phase transformation due to excessively rapid heating. By setting a first and a second platform during heating, the physically adsorbed water can be removed first at the first platform temperature, making the phase transformation reaction at the second platform temperature more complete and thorough. This promotes the rearrangement of the dehydrated skeleton into a high-density phase and the shrinkage to form a gamma-alumina layer with a continuous, dense, rigid three-dimensional network.

[0021] (4) By using atomic layer deposition process to sequentially form an alumina cap layer, a yttrium oxide cap layer and a yttrium fluoride cap layer, a multi-layer dense stacked structure is formed to form a carbon-free all-inorganic wall protection system as a consumable functional layer. It can adapt well to various plasma processing processes containing hydrogen and fluorine. The inner wall of the cavity formed by the inner liner with the above film layer can withstand the severe influence of the cross-etching effect of H and F plasma / free radicals in different processes containing hydrogen and fluorine, ensuring the concentration stability of H and F free radicals in the cavity, thereby achieving cavity wall stabilization under hydrogen and fluorine plasma processes.

[0022] Other advantages of this application will be described in the following detailed description. Attached Figure Description

[0023] Figure 1 This is a flowchart of a method for improving cavity wall stability provided in a preferred embodiment of this application.

[0024] Figure 2 This is a schematic diagram of the structure of a plasma processing device cavity provided in a preferred embodiment of this application.

[0025] In the diagram: 10. Cavity; 11. Inner wall; 12. Air inlet; 13. Heating platform; 14. Exhaust port. Detailed Implementation

[0026] To address the issue that even after sealing, the surface of the anodic aluminum oxide layer on the aluminum liner of the cavity still exhibits some porosity, which, under highly reactive H / F-containing plasma and free radical environments, still leads to some loss of the cavity inner wall surface, resulting in particle shedding and unstable free radical concentration, thus affecting the instability of hydrogen- and fluorine-containing process results, this application provides a method for improving cavity wall stability, comprising the following steps: A cavity liner is provided, the liner material is aluminum alloy, and the working side surface of the liner has an anodized aluminum layer; Using water vapor, the surface of the anodic aluminum oxide layer is hydrated and sealed to form a hydrated aluminum oxide layer on the surface of the anodic aluminum oxide layer. Vacuum baking is performed to cause the hydrated alumina layer to undergo dehydration condensation and phase transformation reaction, forming a dense gamma alumina layer. Using atomic layer deposition, an alumina cap layer, a yttrium oxide cap layer, and a yttrium fluoride cap layer are sequentially formed on the surface of the gamma alumina layer; The liner is installed on the inner wall of a cavity used to perform at least one of a hydrogen-containing plasma treatment process and a fluorine-containing plasma treatment process.

[0027] This application embodiment involves treating the anodic aluminum oxide layer on the surface of the liner with water vapor to form a hydrated aluminum oxide (boehmite) layer. Through baking, the hydrated aluminum oxide layer undergoes dehydration condensation and phase transition reactions to form a dense gamma-alumina (γ-Al2O3) layer. This process pre-completes and solidifies the harmful phase transitions that inevitably occur during the liner's service life in the cavity, ensuring the cavity wall is thermodynamically stable before plasma treatment, effectively mitigating particle generation at its source. Furthermore, by using atomic layer deposition (ALD), an aluminum oxide cap layer, a yttrium oxide cap layer, and a yttrium fluoride cap layer are sequentially formed on the dense gamma-alumina layer, creating a multi-layered, dense, carbon-free, fully inorganic wall protection system. This improves the concentration stability of H and F free radicals within the cavity, achieving cavity wall stabilization under hydrogen- and fluorine-containing plasma processes.

[0028] This application also provides a plasma processing device, including a cavity, the inner wall of which is provided with an inner liner, the inner liner being obtained using the method described above for improving cavity wall stability.

[0029] The specific embodiments of this application will now be described in detail with reference to the accompanying drawings.

[0030] refer to Figure 1 In a first aspect, embodiments of this application provide a method for improving cavity wall stability, which may include the following steps in sequence: Step S11: Provide an inner liner made of aluminum alloy material, the working side surface of which has an anodized aluminum layer.

[0031] refer to Figure 2 In some embodiments, a method for improving cavity wall stability according to an embodiment of this application can be used to improve the cavity wall stability of a plasma processing device (e.g., a plasma debinding device or a plasma surface treatment device) and enhance the process stability of the plasma processing device cavity. The plasma processing device includes a cavity 10, which can be used to perform plasma processing processes using hydrogen-containing gas and / or fluorine-containing gas as the base process gas.

[0032] In some embodiments, the cavity 10 has an inner wall 11, on which a liner (not shown) is applied. The working side surface of the liner facing the cavity constitutes the inner wall surface of the cavity 10. The liner is made of aluminum alloy, and at least the working side of the aluminum alloy surface has an anodized aluminum layer (hard oxide coating). A hot stage 13 is provided in the cavity 10 for placing production wafers (product wafers) to be processed in the plasma processing process, and for maintaining the process temperature during processing by heating and temperature control. An air inlet 12 is provided on the top of the cavity 10 for introducing an excitation gas (a rare gas, such as one or more inert gases like He, Ne, Ar, Kr, etc.) and a process gas used in the plasma processing process (including hydrogen-containing gas, nitrogen-containing gas, fluorine-containing gas, oxygen-containing gas, etc.). The process gas entering the cavity 10 can be excited by the excitation gas in the cavity to form plasma, which is used to process the production wafers placed on the hot stage 13. An exhaust port 14 is provided on the bottom of the cavity 10 for discharging waste gas and controlling the cavity pressure.

[0033] Step S12: Use water vapor to perform a hydration sealing treatment on the surface of the anodic aluminum oxide layer, forming a hydrated aluminum oxide layer on the surface of the anodic aluminum oxide layer.

[0034] Before installing the liner with an anodized aluminum layer on its working side surface onto the inner wall 11 of the cavity 10, the surface of the liner in its component state is treated as follows to form a highly dense protective film layer on its surface. Then, the liner is installed onto the inner wall 11 of the cavity 10 to improve the stability of free radical concentration and reduce particulate defects during hydrogen- and fluorine-containing processes in the cavity.

[0035] In some embodiments, water vapor is used to perform a hydration sealing treatment on the surface of the anodic aluminum oxide layer on the offline liner. The water vapor reacts with the porous alumina (Al₂O₃) on the surface of the anodic aluminum oxide layer to form a hydrated alumina (boehmite, AlOOH) layer. The reaction formula is as follows: Al₂O₃ + H₂O → 2AlOOH Hydrated alumina (boehmite) is a hydroxyl oxide containing structural water and exhibiting a hydrogen-bonded layered structure with low density. Boehmite has an orthorhombic crystal system and a layered structure (AlO6 octahedrons form double-layered structures with shared edges, connected by hydrogen bonds between layers). These interlayer hydrogen bonds are the root cause of its "soft, loose, and scalable" structure. During hydration sealing, it relies on its crystallization and growth within the pores to fill the voids.

[0036] When the porous amorphous anodic aluminum oxide film comes into contact with water vapor, a dissolution-precipitation crystallization process will occur: "surface hydroxylation → weak dissolution of aluminum species → supersaturation in the pores and reprecipitation and crystallization into AlOOH → volume expansion of 30% to 50%, thus wedging the pores".

[0037] Anodized aluminum layers typically have a porous structure with vertical capillary / honeycomb-like nanopores (channels) on their surface. By using water vapor for hydration sealing treatment, the pores on the surface of the anodized aluminum layer can be thoroughly sealed, and the formation of surface flocculent matter can be reduced.

[0038] In some embodiments, prior to hydration sealing, an alkaline cleaning agent (pH=9-10) can be used to ultrasonically degrease the surface of the liner (pretreatment) at a temperature of 45°C-55°C (e.g., 50°C) for 8-12 minutes (e.g., 10 minutes). Afterward, three ultrasonic rinses can be performed using deionized water. Following rinsing, the liner is dried with nitrogen and then baked at 75°C-85°C (e.g., 80°C) for 25-35 minutes (e.g., 30 minutes).

[0039] In some embodiments, pressurized steam sealing (hydration sealing) is performed on the surface of the anodized aluminum layer on the liner using water vapor mixed with an anti-fouling agent. Here, the conventional boiling water immersion method is avoided to reduce the formation of surface flocculent material.

[0040] In some embodiments, the water vapor is prepared using deionized water, and the water vapor has an electrical conductivity of less than 2 μS / cm and a chloride ion content of less than 1 ppm.

[0041] In some embodiments, the anti-fouling agent includes triethanolamine. The amount of triethanolamine added to the water vapor is 0.5 g / L to 2 g / L. By adding the anti-fouling agent to the water vapor, the formation of surface flocculent matter can be effectively reduced.

[0042] In some embodiments, during the hydration sealing treatment, the temperature is 100℃~115℃, the pressure is 0.02MPa~0.05MPa (gauge pressure), and the time is 2min / μm~3min / μm based on the thickness of the anodized aluminum layer. During the hydration sealing treatment, it is important to avoid incomplete sealing due to insufficient sealing time, or excessive sealing time leading to an increase in surface flocculent matter.

[0043] In some embodiments, after hydration sealing, the surface of the liner (anodized aluminum layer with hydrated aluminum oxide layer) can be quickly rinsed with deionized water for 25-35 seconds (e.g., 30 seconds) and dried with nitrogen. Then, immediately (to avoid prolonged moisture absorption), the surface of the liner is subjected to ultrasonic-assisted descaling at a 15%-20% nitric acid solution at 20°C-25°C (room temperature) (to avoid excessive temperature damaging the sealed layer). The ultrasonic frequency is 35kHz-45kHz (low power to assist in peeling off residues at the orifice) for 30-60 seconds (only dissolving surface flocculent formations without damaging the filler) to remove residual ash and discoloration after sealing (no flaky / petal-like morphology on the surface), restoring the surface to a smooth finish (no ash residue when wiped with a white cloth), improving surface quality, and preventing ash stains from affecting subsequent processes. Afterwards, the surface of the liner can be ultrasonically rinsed with deionized water for, for example, three passes, and dried with nitrogen. The rinsing process can only be completed when the resistivity of the deionized water reaches 15 MΩ·cm or higher after the final ultrasonic rinsing.

[0044] Step S13: Perform vacuum baking treatment to cause the hydrated alumina layer to undergo dehydration condensation and phase transformation reaction to form a gamma alumina layer.

[0045] In some embodiments, after deashing, the liner is subjected to vacuum baking, causing the hydrated alumina in the hydrated alumina layer on the surface of the liner (anodic alumina layer) to lose structural water upon heating and undergo a gamma phase transition, transforming into a transition phase alumina (gamma alumina, γ-Al2O3), thus forming a gamma alumina layer on the surface of the anodic alumina layer (hydrated alumina layer). The reaction formula is as follows: 2AlOOH → γ-Al₂O₃ + H₂O↑ Gamma alumina has a cubic crystal system with a defective spinel structure. Oxygen ions form a cubic close-packed framework, while Al ions randomly occupy octahedral and tetrahedral voids (cation vacancy structure). Gamma alumina is a three-dimensional rigid network without interlayer hydrogen bonds, and its hardness and density are much higher than boehmite.

[0046] In some embodiments, vacuum baking processes can be performed using baking equipment such as vacuum ovens or vacuum furnaces.

[0047] In some embodiments, when performing vacuum baking, the vacuum degree is less than 1×10⁻⁶. -3 Torr, preferably with a vacuum degree less than 1×10 -4 Torr allows for faster dehydration and prevents moisture regain.

[0048] In some embodiments, when performing vacuum baking, the heating rate is 2°C / min to 5°C / min to prevent excessively rapid heating from causing stress concentration during phase transformation, which could lead to the formation of microcracks.

[0049] In some embodiments, during the vacuum baking process, two holding platforms, a first platform and a second platform, are set up during the heating phase. The temperature of the first platform (dehydration temperature) is 200℃ to 350℃, for example, 300℃; the holding time of the first platform is 50min to 70min, for example, 60min; the temperature of the second platform (phase change temperature) is 450℃ to 550℃, for example, 500℃; the holding time of the second platform is 2 hours to 4 hours, for example, 3 hours. The first platform temperature and the specific holding time allow for the thorough removal of physically adsorbed water from the hydrated alumina layer, facilitating a more complete and thorough phase change reaction at the second platform temperature. This promotes the rearrangement of the dehydrated framework into a high-density phase and the shrinkage to form a gamma-alumina layer with a continuous, dense, rigid three-dimensional network.

[0050] In some embodiments, during vacuum baking, after the second platform's heat preservation period ends, a cooling phase begins. The cooling rate is 5°C / min or less. For example, the cooling rate may be 5°C / min or less, or 4°C / min or less, or 3°C / min or less, or 2°C / min or less, or 1°C / min or less, but is not limited to these. By performing slow cooling at the aforementioned lower cooling rate, thermal stress cracking of the film layer can be prevented. The oven exit temperature is less than 100°C. For example, the oven exit temperature may be less than 100°C, or less than 90°C, or less than 80°C, or less than 70°C, or less than 50°C, or less than 30°C, or less than 10°C, but is not limited to these.

[0051] The microscopic processes (topological transformations) of boehmite phase transitions may include: (1) At a temperature of about 200℃~350℃, boehmite first removes the interlayer physically adsorbed water and some weakly bound hydroxyl groups, and the interlayer hydrogen bonds begin to break. (2) At a temperature of about 450℃~550℃, the main dehydroxylation stage is the condensation and dehydration of adjacent hydroxyl groups (2-OH →-O- + H2O↑), and the layered structure collapses; (3) The oxygen skeleton basically remains in situ rearranged (topological relationship is preserved), and Al ions are redistributed into spinel lattice sites to form γ-Al2O3.

[0052] In this embodiment, further heating (e.g., above 800°C) should be avoided to prevent the γ phase from eventually transforming into α-Al₂O₃ (corundum) via the δ / θ phase. This is because the γ phase already possesses sufficient density and chemical stability, and the α phase transformation is accompanied by a greater risk of shrinkage and cracking.

[0053] Boehmite has a density of approximately 3.0 g / cm³. 3 The density of γ-Al₂O₃ is approximately 3.5 g / cm³. 3 ~3.7g / cm 3 After dehydration, boehmite loses material (theoretically about 15% weight loss), causing the framework to shrink. The remaining framework rearranges into a high-density phase, and the flocculent / plate-like morphology collapses and shrinks into a continuous, dense body. The loose, layered structure of boehmite, supported by hydrogen bonds, transforms into a rigid three-dimensional Al-O network after the phase transition—its mechanical strength, hardness, and resistance to plasma erosion all increase significantly. This application utilizes the above-described principle. A hydrated alumina layer (boehmite layer) is formed by hydrating and sealing the surface of the anodic alumina layer of the liner. This hydrated alumina layer is then vacuum-baked to induce dehydration condensation and phase transformation, forming a dense gamma-alumina layer. This pre-application vacuum baking process pre-completes and solidifies the harmful phase transformation that inevitably occurs during the liner's service life in the cavity (hydrated alumina inevitably undergoes dehydration shrinkage → stress drift → microcracks → particle generation at the cavity's operating temperature of 150℃~500℃). This ensures that the cavity wall after liner installation is thermodynamically stable before plasma treatment (shifting from "passively enduring wall aging" to "actively eliminating aging sources"). This effectively avoids particle generation at its source, improving the stability of the cavity wall in hydrogen- and fluorine-containing plasma environments.

[0054] In some embodiments, the vacuum baking process can be performed under a full vacuum or a dry nitrogen atmosphere.

[0055] Step S14: Using atomic layer deposition (ALD) technology, an alumina cap layer, a yttrium oxide cap layer, and a yttrium fluoride cap layer are sequentially formed on the surface of the gamma alumina layer.

[0056] In some embodiments, after a dense gamma-alumina layer is formed on the surface of the anodic aluminum oxide layer on the liner by performing sealing and baking processes, an atomic layer deposition process can be used to form an aluminum oxide cap layer (made of Al2O3) on the surface of the gamma-alumina layer to further improve the protective ability of the liner surface.

[0057] By using atomic layer deposition (ALD) technology, a dense alumina cap layer can be formed on the surface of the gamma alumina layer, which can provide good resistance to etching of hydrogen free radicals in hydrogen-containing processes.

[0058] In some embodiments, atomic layer deposition (ALD) equipment, such as batch thermal ALD equipment suitable for processing large parts or single-piece thermal ALD equipment, can be used to perform the ALD process. The volume of the reaction chamber of the ALD equipment must be able to accommodate the liner.

[0059] In some embodiments, a plasma-enhanced atomic layer deposition (PEALD) process can be used to form the alumina cap layer, which can make the alumina cap layer more dense.

[0060] In some embodiments, when forming an alumina cap layer using atomic layer deposition (ALD), the first precursor may include trimethylaluminum (TMA), and the second precursor may include H₂O. The deposition temperature is 200°C to 250°C, for example, 220°C. The number of cycles is 300 to 500 (growth rate approximately 0.1 nm / cycle), for example, 400 cycles. During each cycle, the cycle dosage is: the first precursor (TMA) is introduced for 0.05 s to 0.1 s, for example, 0.08 s; the second precursor (H₂O) is introduced for 0.05 s to 0.1 s, for example, 0.08 s; and the single nitrogen purging time is 10 s to 20 s, for example, 15 s. For the inner lining, CVD mode can be avoided within the aforementioned purging time range.

[0061] In some embodiments, the thickness (target thickness) of the alumina cap layer is 30 nm to 50 nm. For example, the thickness of the alumina cap layer can be 30 nm, 31 nm, 33 nm, 35 nm, 37 nm, 40 nm, 42 nm, 45 nm, 48 nm, or 50 nm, or any value between any two of the aforementioned thickness values. Within the aforementioned thickness range, the deposited alumina cap layer is sufficient to cover the surface of the liner and seal microcracks without generating significant film stress.

[0062] In some embodiments, after the alumina cap layer is formed, an annealing process is performed to further densify the alumina cap layer and remove any residual film. The annealing process may include vacuum annealing. When performing vacuum annealing, the annealing temperature is 280°C to 320°C, for example, 300°C. The annealing time is 1 hour to 2 hours, for example, 1 hour.

[0063] In some embodiments, after forming the alumina cap layer, an atomic layer deposition process is used to further form a stack of a yttrium oxide cap layer (material Y2O3) and a yttrium fluoride cap layer (material YF3) on the surface of the alumina cap layer.

[0064] In some embodiments, an atomic layer deposition process is used to form a yttrium oxide cap layer on the surface of the alumina cap layer. The first precursor can be tris(2,2,6,6-tetramethyl-3,5-heptadecyl)yttrium (Y(thd)3), and it can be transported using a solid-state source heating and evaporation method. The temperature of the Y(thd)3 source bottle is 160°C to 190°C, for example, 175°C. The transport pipeline is heated and temperature-controlled throughout (10°C to 20°C above the source bottle temperature to prevent condensation and blockage). High-purity nitrogen is used as the carrier gas, with a flow rate of 30 SCCM to 100 SCCM, for example, 50 SCCM. The second precursor can be O3, which can be generated using an ozone generator. The concentration of O3 in the transport pipeline is 150 g / Nm³. 3 ~250g / Nm 3 When performing atomic layer deposition, the base pressure is less than 1 × 10⁻⁶. -2 The process pressure is 0.1 Torr to 1 Torr, for example, 0.3 Torr. The liner is placed on a heated base within the reaction chamber of the atomic layer deposition equipment, and the liner is heated to 250°C to 350°C (e.g., 300°C) for atomic layer deposition. The temperature control accuracy of the heated base is ±2°C. The number of cycles is 1000 to 2000 (growth rate approximately 0.04 nm / cycle), for example, 1500 cycles. During each cycle, the cycle dosage is as follows: the introduction time of the first precursor (Y(thd)3) ​​is 0.5 s to 2 s, for example, 1 s; the introduction time of the second precursor (O3) is 1 s to 3 s, for example, 2 s. The single nitrogen purging time is 20s to 60s, for example, 40s. For lining components, the CVD mode can be avoided within the aforementioned purging time range.

[0065] In some embodiments, the thickness (target thickness) of the yttrium oxide cap layer is 40 nm to 80 nm. For example, the thickness of the yttrium oxide cap layer can be 40 nm, 43 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm or 80 nm, or any value between any two of the aforementioned thickness values.

[0066] In some embodiments, after forming the yttrium oxide cap layer, a vacuum annealing process is performed. During vacuum annealing, the annealing temperature is 280°C to 320°C, for example, 300°C. The annealing time is 1 hour to 2 hours, for example, 1.5 hours.

[0067] In some embodiments, after the yttrium oxide cap layer is formed, an atomic layer deposition process can be used to further form a yttrium fluoride cap layer on the surface of the yttrium oxide cap layer in the same reaction chamber.

[0068] In some embodiments, when forming the yttrium fluoride cap layer, the first precursor can be Y(thd)3, which can be transported using a solid-state source heating evaporation method. The Y(thd)3 source bottle temperature is 160°C to 190°C, for example, 175°C. The Y(thd)3 transport pipeline is heated and temperature-controlled throughout (10°C to 20°C above the source bottle temperature to prevent condensation and blockage). High-purity nitrogen is used as the carrier gas, with a flow rate of 30 SCCM to 100 SCCM, for example, 50 SCCM. The second precursor can be TiF4, which can be transported using a solid-state source heating sublimation method. The TiF4 source bottle temperature is 150°C to 200°C, for example, 175°C. The TiF4 transport pipeline is heated and temperature-controlled throughout (10°C to 20°C above the source bottle temperature to prevent condensation and blockage). During atomic layer deposition, the base pressure is less than 1 × 10⁻⁶. -2 The process pressure is 0.1 Torr to 1 Torr, for example, 0.3 Torr. The liner is placed on a heated base in the reaction chamber of the atomic layer deposition equipment, and the liner is heated to a temperature of 175°C to 325°C (preferably 225°C to 325°C, for example 275°C) for atomic layer deposition (below 225°C, C / O / Ti impurities in the film will increase; too low a temperature easily leads to the formation of Y2O3 impurity phase). The temperature control accuracy of the heated base is ±2°C. The number of cycles is 350 to 550 (growth rate is approximately 0.11 nm / cycle to 0.17 nm / cycle), for example, 450 cycles. During each cycle, the cycle dose is: the introduction time of the first precursor (Y(thd)3) ​​is 0.5 s to 2 s (this pulse range exhibits saturation-type self-limiting behavior), for example, the introduction time of the first precursor (Y(thd)3) ​​can be 1 s. The introduction time of the second precursor (TiF4) is 0.5s to 2s, for example, the introduction time of the second precursor (TiF4) can be 1s. The single nitrogen purging time is 20s to 60s, for example, the single nitrogen purging time can be 40s.

[0069] In some embodiments, Y(thd)3 can be replaced by tris(cyclopentadienyl)yttrium (Y(Cp)3), and the Y(Cp)3 source bottle temperature is 120°C to 160°C.

[0070] In some embodiments, TiF4 can be replaced by NH4F (which decomposes upon heating to produce HF and NH3) or by a pyridine hydrogen fluoride complex.

[0071] In some embodiments, a novel HF-free route can be adopted: using a fluorinated organoyttrium precursor and O2 co-reactant, a film (yttrium fluoride cap layer) is formed in one step at a temperature of 275°C to 350°C, which avoids HF corrosion of the reaction chamber.

[0072] In some embodiments, the thickness (target thickness) of the yttrium fluoride cap layer is 40 nm to 80 nm. For example, the thickness of the yttrium fluoride cap layer can be 40 nm, 42 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm or 80 nm, or any value between any two of the aforementioned thickness values.

[0073] In some embodiments, after forming the yttrium fluoride cap layer, a vacuum annealing process is performed. During vacuum annealing, the annealing temperature is 280°C to 320°C, for example, 300°C. The annealing time is 1 hour to 2 hours, for example, 1.5 hours.

[0074] By using atomic layer deposition (ALD) technology, a dense yttrium oxide cap layer and a yttrium fluoride cap layer can be formed on the surface of the alumina cap layer, which can provide good anti-etching effect against fluorine free radicals in fluorine-containing processes.

[0075] In some embodiments, an atomic layer deposition process is used to sequentially and alternately form yttrium oxide cap layers and yttrium fluoride cap layers on the surface of an alumina cap layer. The yttrium oxide and yttrium fluoride cap layers are stacked alternately to form a multi-layer structure, with each yttrium oxide cap layer being a single-atom yttrium oxide layer formed in a single cycle, and each yttrium fluoride cap layer being a single-atom yttrium fluoride layer formed in a single cycle, forming a composite cap layer. The total thickness of the composite cap layer can be 50 nm to 200 nm.

[0076] Step S15: Install the liner onto the inner wall of the cavity.

[0077] In some embodiments, after forming a yttrium oxide cap layer and a yttrium fluoride cap layer on the surface of the alumina cap layer, the surface treatment of the liner is completed. Then, the liner can be installed on the inner wall of the cavity 10, with the working side surface of the liner facing the cavity forming the inner wall surface of the cavity 10. At this time, the cavity 10 equipped with the liner obtained by the method for improving cavity wall stability provided in the embodiments of this application can be used to perform at least one of a hydrogen-containing plasma process and a fluorine-containing plasma process.

[0078] The aluminum alloy liner has an anodic aluminum oxide layer, a hydrated aluminum oxide layer, a gamma aluminum oxide layer, an aluminum oxide cap layer, a yttrium oxide cap layer, and a yttrium fluoride cap layer on its working side surface facing the cavity, forming a multi-layered protective system. This improves the protective capability of the liner surface, reduces the probability of H and F plasma / free radicals penetrating the inner wall surface, and further reduces the residue and reaction inside the porous structure of the anodic aluminum oxide layer, thus improving the concentration stability of H and F free radicals in the cavity.

[0079] Furthermore, by using atomic layer deposition to sequentially form a multi-layered, dense stacked structure of alumina cap layer, yttrium oxide cap layer, and yttrium fluoride cap layer, a carbon-free, all-inorganic wall protection system is constructed as a consumable functional layer. This system can well adapt to various plasma processing processes containing hydrogen and fluorine. The inner wall of the cavity formed by the liner with the above-mentioned film layers can withstand the severe effects of the cross-etching of H and F plasmas / free radicals in different processes containing hydrogen and fluorine, ensuring the concentration stability of H and F free radicals in the cavity, thereby achieving cavity wall stabilization under hydrogen-containing and fluorine-containing plasma processing processes.

[0080] In a second aspect, a plasma processing apparatus according to an embodiment of this application includes a cavity, the inner wall of which is provided with an inner liner, the inner liner being obtained using the method for improving cavity wall stability provided in any of the embodiments of the first aspect described above.

[0081] refer to Figure 2 In some embodiments, the plasma processing equipment may include a plasma adhesive removal device or a plasma surface treatment device. The cavity 10 provided in the plasma processing equipment is a plasma processing cavity and can be used to perform a plasma processing process using hydrogen-containing gas and / or fluorine-containing gas as the base process gas.

[0082] In some embodiments, the cavity 10 has an inner wall 11, on which a liner (not shown) is applied. The working side surface of the liner facing the cavity constitutes the inner wall surface of the cavity 10. The liner is made of aluminum alloy, and at least the working side of the aluminum alloy surface is sequentially provided with an anodic aluminum oxide layer (hard oxide coating), a hydrated aluminum oxide layer, a gamma aluminum oxide layer, an aluminum oxide cap layer, a yttrium oxide cap layer, and a fluorinated yttrium cap layer. A hot stage 13 is provided at the bottom of the cavity 10 for placing the production wafer (production wafer) to be processed in the plasma processing process, and the temperature can be controlled by a heating and temperature control device provided on the hot stage 13 to maintain the process temperature during processing. An air inlet 12 is provided at the top of the cavity 10 for introducing excitation gas (a rare gas, such as one or more inert gases such as He, Ne, Ar, Kr, etc.) and process gas used in the plasma processing process (including hydrogen-containing gas, nitrogen-containing gas, fluorine-containing gas, oxygen-containing gas, etc.). The process gas entering the cavity 10 is excited by the excited gas in the cavity to form plasma, which is used to perform plasma treatment on the production wafers placed on the hot stage 13. An exhaust port 14 is provided at the bottom of the cavity 10 for discharging waste gas and controlling the cavity pressure.

[0083] Before the liner is installed on the inner wall of the cavity, the method for improving the stability of the cavity wall provided in the above-described embodiments of this application is used to form a hydrated alumina layer, a gamma alumina layer, an alumina cap layer, a yttrium oxide cap layer, and a fluoride cap layer on the surface of the anodic alumina layer. After being installed on the inner wall of the cavity, the liner is used to resist the cross-etching effect of H and F plasma / free radicals in the plasma processing process, improve the concentration stability of H and F free radicals in the cavity 10, and prevent particles from falling off, thereby improving the stability of the cavity wall in the hydrogen-containing and fluorine-containing plasma environment.

[0084] In summary, this embodiment of the application forms a hydrated alumina (boehmite) layer by performing a water vapor hydration sealing treatment on the anodic alumina layer on the surface of the liner. Through baking, the hydrated alumina layer undergoes dehydration condensation and phase transformation reaction to form a dense gamma alumina (γ-Al2O3) layer. This can complete and solidify the harmful phase transformation that will inevitably occur during the service of the liner in the cavity in advance, so that the cavity wall after the liner is installed enters a thermodynamically stable state before the plasma treatment process, effectively avoiding the source of particle generation. Furthermore, by using atomic layer deposition, an alumina cap layer, a yttrium oxide cap layer, and a yttrium fluoride cap layer are sequentially formed on the dense gamma alumina layer, forming a carbon-free, fully inorganic wall protection system with a multi-layered, dense stacked structure. This can improve the concentration stability of H and F free radicals in the cavity and reduce particle shedding defects, achieving cavity wall stabilization under hydrogen- and fluorine-containing plasma processes.

[0085] The above are merely preferred embodiments of this application. These embodiments are not intended to limit the scope of protection of this application. Therefore, any equivalent changes made based on the description and drawings of this application should also be included within the scope of protection of this application.

Claims

1. A method for improving cavity wall stability, characterized in that, In order, they include: A cavity liner is provided, the liner material is aluminum alloy, and the working side surface of the liner has an anodized aluminum layer; Using water vapor, the surface of the anodic aluminum oxide layer is hydrated and sealed to form a hydrated aluminum oxide layer on the surface of the anodic aluminum oxide layer. Vacuum baking is performed to cause the hydrated alumina layer to undergo dehydration condensation and phase transformation reaction, forming a dense gamma alumina layer. Using atomic layer deposition, an alumina cap layer, a yttrium oxide cap layer, and a yttrium fluoride cap layer are sequentially formed on the surface of the gamma alumina layer; The liner is installed on the inner wall of a cavity used to perform at least one of a hydrogen-containing plasma treatment process and a fluorine-containing plasma treatment process.

2. The method for improving cavity wall stability according to claim 1, characterized in that, The water vapor is prepared using deionized water, and an anti-ashing agent is added to the water vapor. The electrical conductivity of the water vapor is less than 2 μS / cm, and the chloride ion content is less than 1 ppm. When performing the hydration sealing treatment, the temperature is 100℃~115℃, the pressure is 0.02MPa~0.05MPa, and the time is 2min / μm~3min / μm.

3. The method for improving cavity wall stability according to claim 2, characterized in that, The anti-ashing agent includes triethanolamine added at a rate of 0.5 g / L to 2 g / L; and / or, after the hydration sealing treatment, the surface of the liner is rinsed with deionized water for 25 s to 35 s and dried with nitrogen. Then, the surface of the liner is subjected to ultrasonic-assisted deashing treatment with a volume concentration of 15% to 20% nitric acid solution at room temperature for 30 s to 60 s, with an ultrasonic frequency of 35 kHz to 45 kHz. Afterward, the surface of the liner is ultrasonically rinsed multiple times with deionized water until the resistivity of the deionized water after the final ultrasonic rinsing reaches 15 MΩ·cm or higher, and then dried with nitrogen.

4. The method for improving cavity wall stability according to claim 1, characterized in that, When performing the vacuum baking process, the vacuum level is less than 1×10⁻⁶. -3 Torr, with a heating rate of 2℃ / min to 5℃ / min, a first plateau temperature of 200℃ to 350℃, a first plateau holding time of 50min to 70min, a second plateau temperature of 450℃ to 550℃, a second plateau holding time of 2 hours to 4 hours, a cooling rate of less than 5℃ / min, and a furnace exit temperature of less than 100℃.

5. The method for improving cavity wall stability according to claim 1, characterized in that, When forming the alumina cap layer, the first precursor includes trimethylaluminum, the second precursor includes H2O, the temperature is 200℃~250℃, the number of cycles is 300 to 500, the introduction time of the first precursor is 0.05s~0.1s in each cycle, the introduction time of the second precursor is 0.05s~0.1s, the single purging time is 10s~20s; and / or, the thickness of the alumina cap layer is 30nm~50nm.

6. The method for improving cavity wall stability according to claim 1, characterized in that, When forming the yttrium oxide cap layer, the first precursor includes tris(2,2,6,6-tetramethyl-3,5-heptadecyl)yttrium, the second precursor includes O3, the temperature is 250℃~350℃, the number of cycles is 1000 to 2000, the introduction time of the first precursor is 0.5s~2s in each cycle, the introduction time of the second precursor is 1s~3s, the single purging time is 20s~60s; and / or, the thickness of the yttrium oxide cap layer is 40nm~80nm.

7. The method for improving cavity wall stability according to claim 1, characterized in that, When forming the yttrium fluoride cap layer, the first precursor includes tris(2,2,6,6-tetramethyl-3,5-heptadecyl)yttrium, the second precursor includes TiF4, the temperature is 175℃~325℃, the number of cycles is 350 to 550, the introduction time of the first precursor is 0.5s~2s per cycle, the introduction time of the second precursor is 0.5s~2s, the single purging time is 20s~60s; and / or, the thickness of the yttrium fluoride cap layer is 40nm~80nm.

8. The method for improving cavity wall stability according to claim 1, characterized in that, After the alumina cap layer, the yttrium oxide cap layer, and the yttrium fluoride cap layer are formed, each is subjected to an annealing treatment.

9. The method for improving cavity wall stability according to claim 8, characterized in that, The annealing process includes vacuum annealing at a temperature of 280℃ to 320℃ for 1 to 2 hours.

10. A plasma processing device, characterized in that, The device includes a cavity, the inner wall of which is provided with an inner liner, the inner liner being obtained using the method for improving cavity wall stability as described in any one of claims 1-9.